Unique peptide maps of the three largest proteins specified by the flavivirus Kunjin. - Wright, P J (1977)
Tryptic digests of four polypeptides found in Kunjin virus-infected Vero cells, NV5, NV4, V3, and NV3, were compared by peptide mapping. The polypeptides to be analyzed were labeled with radioactive methionine and separated by electrophoresis through polyacrylamide gels containing sodium dodecyl sulfate. Because infection of Vero cells by Kunjin virus does not inhibit host cell protein synthesis, radioactively labeled viral polypeptides prepared from infected cells migrate coincidentally during sodium dodecyl sulfate-gel electrophoresis with some of the labeled host proteins. Thus, the genuine viral methionine-containing peptides in tryptic digests of viral proteins have been identified by co-analyzing polypeptides from [3H]methionine-labeled uninfected cells and [35S]methionine-labeled infected cells and determining the 35S/3H ratio in the peptides resolved in two dimensions on thin-layer chromatography plates. The peptide map of NV3 demonstrated that it is host coded, whereas NV5, NV4, and V3 have unique peptide maps and, therefore, account for approximately one-half of the coding potential of Kunjin virus RNA.